Induction of sleep apnoea with negative pressure ventilation in patients with chronic obstructive lung disease. - Levy, R D (1992)
BACKGROUND: Negative pressure ventilation provides intermittent non-invasive ventilatory assistance for patients with advanced chronic obstructive lung disease. Upper airway obstruction during sleep, a reported complication of the technique, may, however, limit its clinical applicability. METHODS: The effects of nocturnal negative pressure ventilation on ventilation and on indices of sleep quality were investigated in five patients with severe chronic obstructive lung disease (mean (SE) FEV1 31% (3%) predicted) who had completed three months of nightly negative pressure ventilation. Subjects underwent overnight polysomnography on consecutive nights, the first night serving as a control and negative pressure ventilation being provided on the second night. Ventilators were adjusted to result in maximum suppression of the peak phasic electromyogram signal from the diaphragm. RESULTS: Negative pressure ventilation resulted in substantial increases in episodes of obstructive apnoea and hypopnoea (mean (SE)/h 59.3 (19.8) v 3.2 (1.3) on control nights). Most obstructive events, however, were associated with under 3% oxygen desaturation, and the lowest recorded values for overnight oxygen saturation were similar on the two study nights. Negative pressure ventilation was also associated with significant increases in the frequencies of movement arousals and changes in sleep stage. CONCLUSIONS: Negative pressure ventilation applied during sleep to patients with advanced chronic obstructive lung disease may result in the development of recurrent episodes of apnoea and hypopnoea as well as altered sleep quality, which could limit its clinical applicability.